A diseasome cluster-based drug repurposing of soluble guanylate cyclase activators from smooth muscle relaxation to direct neuroprotection. (December 2018) - Langhauser, Friederike; Casas, Ana; Dao, Vu-Thao-Vi; Guney, Emre; Menche, Jörg; Geuss, Eva; Kleikers, Pamela; López, Manuela; Barabási, Albert-L.; Kleinschnitz, Christoph; Schmidt, Harald
Abstract Network medicine utilizes common genetic origins, markers and co-morbidities to uncover mechanistic links between diseases. These links can be summarized in the diseasome, a comprehensive network of disease–disease relationships and clusters. The diseasome has been influential during the past decade, although most of its links are not followed up experimentally. Here, we investigate a high prevalence unmet medical need cluster of disease phenotypes linked to cyclic GMP. Hitherto, the central cGMP-forming enzyme, soluble guanylate cyclase (sGC), has been targeted pharmacologically exclusively for smooth muscle modulation in cardiology and pulmonology. Here, we examine the disease associations of sGC in a non-hypothesis based manner in order to identify possibly previously unrecognized clinical indications. Surprisingly, we find that sGC, is closest linked to neurological disorders, an application that has so far not been explored clinically. Indeed, when investigating the neurological indication of this cluster with the highest unmet medical need, ischemic stroke, pre-clinically we find that sGC activity is virtually absent post-stroke. Conversely, a heme-free form of sGC, apo-sGC, was now the predominant isoform suggesting it may be a mechanism-based target in stroke. Indeed, this repurposing hypothesis could be validated experimentally in vivo as specific activators of apo-sGC were directly neuroprotective, reduced infarct size and increased survival. Thus, common mechanism clusters of the diseasome allow direct drug repurposing across previously unrelated disease phenotypes redefining them in a mechanism-based manner. Specifically, our example of repurposing apo-sGC activators for ischemic stroke should be urgently validated clinically as a possible first-in-class neuroprotective therapy. Systems based pharmacology: drug repurposing by diseasome Systems medicine utilizes common genetic origins and co-morbidities to uncover mechanistic links between diseases, which are summarized in the diseasome. Shared pathomechanisms may also allow for drug repurposing within these disease clusters. Here, Schmidt and co-workers show indeed that, based on this principle, a cardio-pulmonary drug can be surprisingly repurposed for a previously not recognised application as a direct neuroprotectant. They find that the cyclic GMP forming soluble guanylate cyclase becomes dysfunctional upon stroke but regains catalytic activity in the presence of specific activator compounds. This new mechanism-based therapy should be urgently validated clinically as a possible first-in-class treatment in stroke.